Structured care after a DSD diagnosis in childhood: a mixed methods evaluation of the Empower-DSD program - Wechsung, Katja; Marshall, Louise; Jürgensen, Martina; Wiegmann, Sabine; Kalender, Ute; Brösamle, Manuela; Herrmann, Gloria; Hiort, Olaf; Janssen-Schmidchen, Gerda; Richter-Unruh, Annette; Wabitsch, Martin; Wunn, Charlotte; et al. (Frontiers in Pediatrics, 2025)
IntroductionDifferences of sex development (DSD) encompass several rare diagnoses with medical and social implications. If a child is suspected of having DSD, timely and comprehensive information to the family is crucial for an undisturbed parent-child relationship and a good outcome. Providing information and competent care for a child with DSD is challenging for medical staff and parents, especially at the beginning of care, when many diagnostic results are still pending. The Empower-DSD information management program provides a structured multidisciplinary care and information exchange for children and their parents in the first 8–12 weeks after presenting to a specialized DSD center.MethodsFrom June 2020 to August 2022, 51 families completed the structured care pathway in 4 DSD centers in Germany as part of the government-funded Empower-DSD study. The program was evaluated with a quantitative and a qualitative approach. Diagnosis, age of child, total duration, number of appointments, and completed elements of care were documented. Semi-structured guided interviews with parents, peers and professionals were used to explore expectations and the experience of the involved stakeholders.ResultsCare elements were documented in 11 children with congenital adrenal hyperplasia (CAH) and 28 children with other DSD-diagnoses (chromosomal DSD; 46, XY-DSD; 46, XX-DSD) with a mean age of 1.8 years (0–18 years). In total 45 people were interviewed. The information management program alleviated stress and uncertainties for parents and encouraged a trusting relationship with the DSD team. Professionals rated the developed materials as a valuable tool to provide consistent and thorough care. Parents underlined the importance of the early access to specialized DSD teams, a clear and open communication and the reassuring attitude of professionals in DSD care. Parents and professionals stated that the program required time and resources and would prefer an individualized approach instead of a predefined duration.ConclusionThe structured, multidisciplinary support within the first weeks after a DSD diagnosis was perceived to be of high quality by all stakeholders involved. Information on the nature of the decision-making process and peer narratives could be added to the information material.